Rituximab in steroid-refractory immune-related pancreatitis: a case report - Santoro, Armando; Masini, Silvia; Cavina, Raffaele; Tronconi, Maria Chiara; De Vincenzo, Fabio (Frontiers in Oncology, 2023)
The use of immune checkpoint inhibitors (ICIs) for treating several types of cancers is increasing, but they may be associated with immune-related adverse events (irAEs). Pancreatitis is a rare irAE, mostly responsive to steroid treatment. There are no published data on the management of steroidrefractory ICI-induced pancreatitis. Rituximab has shown efficacy in the setting of relapsing non-ICIinduced autoimmune pancreatitis. However, its use has not been tested for treating immunotherapyrelated pancreatitis. Here, we present a case of a patient with steroid-refractory immune-related pancreatitis successfully treated with rituximab as a potential strategy for irAE management.